Fluxes of carbon and water in Cyperus papyrus L. tropical wetlands - Saunders, Matthew (Trinity College (Dublin, Ireland). Department of Botany, 2006)
Carbon dioxide (CO2 ), water vapour (H2O) and energy fluxes play important roles in the functioning of vegetative ecosystems and also influence the climate of our planet at both the regional and global scale through important feedback mechanisms. Tropical wetlands cover a very small proportion of the total continental land mass but because they are highly productive their contribution to global primary production far outweighs their limited distribution. Fluxes of CO2 , H2O and energy were measured using eddy covariance techniques from a stand of the C4 emergent sedge Cyperus papyrus L. at the Kirinya West wetland, Jinja, Uganda and a formerly pristine papyrus wetland, but now dominated by Colocasia antiquorum (cocoyam) cultivation at the Nakivubo wetland, Kampala, Uganda.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin